2004
DOI: 10.1641/0006-3568(2004)054[0767:trobit]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Biodiversity in the Functioning of Freshwater and Marine Benthic Ecosystems

Abstract: Empirical studies investigating the role of species diversity in sustaining ecosystem

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
212
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 322 publications
(218 citation statements)
references
References 65 publications
(73 reference statements)
5
212
0
1
Order By: Relevance
“…However, although highly productive species do indeed make consistent and sizeable contributions to plant biodiversity effects, these are equaled or exceeded in frequency and magnitude by multispecies contributions to biomass. Our finding that the net effects of plant diversity on biomass are generally positive corroborates what appears to hold true for many types of organisms in ecosystems around the globe (10,11,(13)(14)(15)36). However, our finding that diverse polycultures tend to achieve less biomass than their most productive species contrasts with a common prediction in diversity-function research.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, although highly productive species do indeed make consistent and sizeable contributions to plant biodiversity effects, these are equaled or exceeded in frequency and magnitude by multispecies contributions to biomass. Our finding that the net effects of plant diversity on biomass are generally positive corroborates what appears to hold true for many types of organisms in ecosystems around the globe (10,11,(13)(14)(15)36). However, our finding that diverse polycultures tend to achieve less biomass than their most productive species contrasts with a common prediction in diversity-function research.…”
Section: Discussionsupporting
confidence: 81%
“…Studies analyzed here are a subset of those reviewed by Cardinale et al (14) but for which extensive amounts of new data were collected. Studies were identified from a literature search in which authors collated reference lists from recent surveys of biodiversity-ecosystem functioning research (9,10,18,35,36), supplemented with a search of the Institute for Scientific Information Web of Knowledge database, using the keyword sequence species AND (diversity OR richness) AND (community OR ecosystem) AND (function OR functioning OR production OR productivity OR biomass). More than 200 articles published through 2005 were reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic fingerprint of the microbial community provides information on the presence and relative abundance of the species and thus indicates biodiversity. In macro-ecology, a high biodiversity is considered as a good sign for environmental quality, while contamination is likely to decrease the species richness (Covich et al 2004). Contamination is also reported to decrease the biodiversity of the invertebrate fauna in groundwater (Griebler and Mösslacher 2003).…”
Section: Bioindicators For Groundwater Qualitymentioning
confidence: 99%
“…A number of recently published reviews and meta-analyses indicate that functioning is positively related to richness (Covich et al, 2004;Hillebrand and Cardinale, 2004;Balvanera et al, 2006;Cardinale et al, 2006), particularly with respect to biomass accumulation (Downing, 2005), resource use efficiency (Cardinale et al, 2006) and stability (Balvanera et al, 2006). However, there is ample evidence supporting a situation where community composition and species identity may be as important as species richness in determining ecosystem functioning (Covich et al, 2004;Downing, 2005;Cardinale et al, 2006). Pioneering studies focused on species richness as a measure of diversity, most commonly in studies of a single ecosystem process (Reiss et al, 2009).…”
Section: Introductionmentioning
confidence: 99%